A common unemployment insurance system for the Euro area - Sebastian Dullien; Ferdinand Fichtner (DIW Economic Bulletin, 2013)
A European transfer system could contribute to stabilization of the euro area by synchronizing business cycles in the monetary union, thus simplifying the common monetary policy. Such a system is proposed here in the form of a European unemployment insurance scheme. Compared to other forms of fiscal transfer systems, this has some advantages: by putting the focus on short-term unemployment, an automatic link between payments and the cyclical situation of a member state is ensured, making the system relatively robust against political manipulation. Furthermore, this set-up will most likely prevent a case in which countries systematically become net recipients or net contributors. Therefore, the risk of permanently creating transfers to single countries is low. While a European unemployment insurance system would not be suitable for removing or eliminating structural discrepancies between countries (such as those that caused the euro crisis), cyclical imbalances within a monetary union would be effectively dampened, at not much additional administrative cost. Such a system could thus become an important stabilizing element for the member states of the European Monetary Union.
Keywords: E32; E63; F41; 330; economic stabilization; European integration; unemployment insurance